1988
DOI: 10.1037/0022-0663.80.2.159
|View full text |Cite
|
Sign up to set email alerts
|

Effect of interest on attention and learning.

Abstract: The effects of interest on the allocation of attention to, and the learning of, written material were investigated in this study. Twenty-three college students read 72 sentences that had been previously rated for interest. The sentences were presented on an Apple IIe microcomputer that recorded two measures of attention: sentence reading time and reaction time to a secondary task. After sentence presentation, students were given a cued recall test of the material. Results showed that although interesting sente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
2

Year Published

1990
1990
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(56 citation statements)
references
References 24 publications
3
51
2
Order By: Relevance
“…The main ideas, on the other hand, were probably memorable because of the combined effect of structural importance and interest. Previous research has found that important information is better recalled than unimportant information (e.g., , and interesting information is recalled better than uninteresting information (Anderson et al, 1984;Shirey & Reynolds, 1988). However, the interestingness of the main ideas in this passage was qualitatively different than that of the seductive details.…”
Section: Discussionmentioning
confidence: 44%
“…The main ideas, on the other hand, were probably memorable because of the combined effect of structural importance and interest. Previous research has found that important information is better recalled than unimportant information (e.g., , and interesting information is recalled better than uninteresting information (Anderson et al, 1984;Shirey & Reynolds, 1988). However, the interestingness of the main ideas in this passage was qualitatively different than that of the seductive details.…”
Section: Discussionmentioning
confidence: 44%
“…The results reported here do not purport that all interesting material should be avoided, for previous research has consistently shown that students learn better when the material is interesting as opposed to when it is not (Hidi & Baird, 1986;Shirey & Reynolds, 1988;Wade, 1992). Perhaps the challenge is to find a way to present science lessons in a way that is interesting, without resorting to the use of entertaining but irrelevant details.…”
Section: Limitations and Future Directionsmentioning
confidence: 80%
“…For example, while reading about how lightning works, the reader may select and retain seductive information about golfers who were killed by lightning rather than information about the interaction of positive and negative charges within a cloud. This may be because seductive details tend to contain information that requires little attentional effort and is easily understood (Shirey & Reynolds, 1988).…”
Section: The Distraction Hypothesismentioning
confidence: 99%
“…Thus, the video clips are analogous to seductive details in text passages, which can be defined as interesting but conceptually irrelevant material that is added to a passage to arouse the learner's interest (Garner, Brown, Sanders, & Menke, 1992;Garner, Gillingham, & White, 1989). Research on seductive details in a book-based environment has shown that adding interesting but conceptually irrelevant text to a text passage can reduce the amount of relevant material that the learner remembers (Garner et al, 1992(Garner et al, , 1989Hidi & Baird, 1988;Mohr, Glover, & Ronning, 1984;Shirey & Reynolds, 1988;Wade & Adams, 1990). Similarly, Harp & Mayer (1997 reported that adding interesting but conceptually irrelevant illustrations to a text-andillustrations explanation results in poorer performance on tests of retention and transfer.…”
Section: Figure 1 (Continued)mentioning
confidence: 99%